NEW REVIVALISME ISLAM - Murkilim Murkilim (Universitas Islam Negeri Fatmawati Sukarno, 2017)
New Islamic revivalism is a contemporary Islamic thought movement that seeks to cleanse and restore the understanding and practice of Islamic teachings to pure Islam. New Revivalism arises because of the internal prob- lems of Muslims and External and Western modem influences. New Revivalism in Pakistan emerged under the main character of Abul ‘A’la Al-Mawdudi with the idea that the life of Muslims should be governed by Islamic teachings in an Islamic state, which takes the form of “theo democracy”. For the realization of such a state, a gradual Islamic revolution should be undertaken, by first doing the Islamization of society. Hasan Al Bana with Kaffahnya Islamic concept through lkhwanu Muslimin trying to make it happen by utilizing all available potential, either individually or institutionally, so that Islam becomes a comprehensive, universal ldiology based on the original source; Al-qur’an and Sunnah. The Mus- lim Brotherhood movement became radicalized in the hands of Sayyid Qutub, so ready to conduct jihad fisabilillah. In Indonesia also found the movement of Revivalism both in the form of premodernist and postmodernist among others is padri movement, Muhammadiyah, The United of Islam, and in the form of more now among others is Jamaat Islam and Darul Arkam. Keywords: revivalism, Islam